Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Sure! Let's solve the system of equations step-by-step:
[tex]\[ \left\{\begin{array}{c} 2x + y = 11 \\ y = x + 2 \\ \end{array}\right. \][/tex]
1. Substitute [tex]\( y \)[/tex] from the second equation into the first equation:
The second equation gives us:
[tex]\[ y = x + 2 \][/tex]
Substituting this expression for [tex]\( y \)[/tex] into the first equation:
[tex]\[ 2x + (x + 2) = 11 \][/tex]
2. Simplify and solve for [tex]\( x \)[/tex]:
Combine like terms:
[tex]\[ 2x + x + 2 = 11 \][/tex]
Simplify:
[tex]\[ 3x + 2 = 11 \][/tex]
Subtract 2 from both sides:
[tex]\[ 3x = 9 \][/tex]
Divide by 3:
[tex]\[ x = 3 \][/tex]
3. Substitute [tex]\( x = 3 \)[/tex] back into the second equation to find [tex]\( y \)[/tex]:
Using the second equation [tex]\( y = x + 2 \)[/tex]:
[tex]\[ y = 3 + 2 \][/tex]
Simplify:
[tex]\[ y = 5 \][/tex]
So, the solution to the system of equations is:
[tex]\[ x = 3, \quad y = 5 \][/tex]
Therefore, the solution to the given system of equations is [tex]\((x, y) = (3, 5)\)[/tex].
[tex]\[ \left\{\begin{array}{c} 2x + y = 11 \\ y = x + 2 \\ \end{array}\right. \][/tex]
1. Substitute [tex]\( y \)[/tex] from the second equation into the first equation:
The second equation gives us:
[tex]\[ y = x + 2 \][/tex]
Substituting this expression for [tex]\( y \)[/tex] into the first equation:
[tex]\[ 2x + (x + 2) = 11 \][/tex]
2. Simplify and solve for [tex]\( x \)[/tex]:
Combine like terms:
[tex]\[ 2x + x + 2 = 11 \][/tex]
Simplify:
[tex]\[ 3x + 2 = 11 \][/tex]
Subtract 2 from both sides:
[tex]\[ 3x = 9 \][/tex]
Divide by 3:
[tex]\[ x = 3 \][/tex]
3. Substitute [tex]\( x = 3 \)[/tex] back into the second equation to find [tex]\( y \)[/tex]:
Using the second equation [tex]\( y = x + 2 \)[/tex]:
[tex]\[ y = 3 + 2 \][/tex]
Simplify:
[tex]\[ y = 5 \][/tex]
So, the solution to the system of equations is:
[tex]\[ x = 3, \quad y = 5 \][/tex]
Therefore, the solution to the given system of equations is [tex]\((x, y) = (3, 5)\)[/tex].
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.